Description of the male of Chlorotabanus leucochlorus Fairchild (Diptera, Tabanidae) - Krolow, Tiago Kütter; Henriques, Augusto Loureiro (Revista Brasileira de Entomologia, 2008)
The male of Chlorotabanus leucochlorus Fairchild, 1961 is described for the first time. The species is known from northern Brazil, Suriname, Venezuela and eastern Peru. Seven males from various locations in the state of Amazonas, Brazil were examined. The material was deposited in the Invertebrate Collections of the Instituto Nacional de Pesquisas da Amazônia (INPA) and Zoological Collection Paulo Bührnheim (UFAM), both in Manaus, Brazil.
Descrição do macho de Chlorotabanus leucochlorus Fairchild (Diptera, Tabanidae)
Keywords: Brachycera; Chlorotabanus; Diptera; Equidae; Invertebrata; Tabanidae